Core Model of Accountancy Education and Initial Professional Development in University - Level Programs in Albania - Ramaj, Brisejda Zenuni (European Journal of Multidisciplinary Studies, 2022)
Factors affecting accounting education Accounting is not developed uniformly around the world because it is influenced by factors such as social, cultural, political, economic and legal development, which are different in different countries. Although, there is still a large-scale diversification, in the second decade of our century there is an increasing trend towards convergence between different accounting systems in the world. University-level programs may be recognized by statute or law, but they may not be recognized and evaluated by market demands or other bodies. Recognition and evaluation of undergraduate programs can focus on their content, duration, and quality. Analyzing the data collection in Albania.
Keywords: International education standards, business organizations, study programs, Initial professional development